Sifilis Laten Pada Kehamilan : Case Report - Agoeng Basoeki, Rijanto; Nadiatul, Adisty; Amelia, Kamila; Tri Wahyuni, Kartika (Universitas Muhammadiyah Surabaya, 2025)
Background: Latent syphilis is asymptomatic and only shows reactive serological test results. Syphilis in pregnancy can cause recurrent abortion, neonatal morbidity and mortality. Objective: To report a case of latent syphilis in pregnancy. Case Presentation: A 27-years old woman, GIIIP20002, at 38 weeks of gestation, came to the emergency department at Soegiri Hospital, with reactive syphilis. Currently the patient does not complain of any complaints. The patient was screened for syphilis during the first antenatal visit at the health facility. Dermatological and venereological status were within normal limits. Laboratory test results VDRL/RPR reactive 1:16. TPHA reactive 1:5120. Benzathine penicillin is the main therapy in the treatment of syphilis in pregnant women. Conclusion: Latent Syphilis in pregnancy is the most common congenital infection worldwide and has tremendous consequences for the mother and her developing fetus if left untreated. The diagnosis is based on reactivity Treponemal and nonTreponemal serological test result. Therefore, the choice of caesarean section is the main choice to reduce the risk of transmission to the fetus.